Detrital zircon ages, provenance and tectonic evolution in the early Paleozoic of Tasmania and Waratah Bay, Victoria. Issue 5 (4th July 2022) - Habib, U.; Meffre, S.; Berry, R.; Kultaksayos, S.
Abstract: The provenance of the upper Cambrian to Upper Ordovician sedimentary rocks of Tasmania and Waratah Bay in southern Victoria provides information about the complex and dynamic tectonic environment present during their deposition. This paper uses U–Pb detrital zircon data to constrain stratigraphic comparisons and tectonic reconstructions of these rock sequences. Multivariate statistics are used to investigate the similarity between the U–Pb ages and quantify the disparity among different samples from various locations. In western and central Tasmania, the Tyennan region supplied most detrital zircons during the late Cambrian and Early Ordovician. The overlying Middle Ordovician Pioneer Sandstone records a switch in provenance with zircons derived from the Mount Read Volcanics (MRV) mixed with zircons similar to those from continental-derived Paleozoic sedimentary rocks deposited throughout east Gondwana. The Middle to Upper Ordovician Gordon Group in western and central Tasmania lacks detrital zircons younger than 1.2 Ga, which indicates a return to a local provenance from Precambrian rocks. In southern Tasmania, the switch to zircons derived from the MRV and east Gondwana-like sources occurred earlier within the Cambrian Deadmans Bay Formation, which is dominated by the east Gondwana Paleozoic zircon age signature. In the East Tasmania Terrane, Ordovician sedimentary rocks from Lefroy have detrital zircon populations dominated by Neoproterozoic and earliest Paleozoic sources similar to the Ordovician sedimentary rocks in the Lachlan Orogen. In southern Victoria, the Bear Gully Chert from Waratah Bay exhibit both Tyennan and distal Gondwana detrital sources. The switching of detrital zircon sources in the west Tasmanian sedimentary sequences implies the docking of Tasmania with mainland Australia during the Cambrian Tyennan Orogeny. The arrival of the distal zircons into these basins occurred at different times in the different areas, reflecting a complex local topography and paleogeography. Key Points: Paleozoic sedimentary rocks in Tasmanian exhibit multisource detrital U–Pb age signatures that change over time, implying tectonic activity during their deposition. Paleozoic sedimentary rocks in northeastern Tasmania show Gondwana-wide detrital signatures similar to Lachlan Orogen. The Ordovician Bear Gully Chert at Waratah Bay in southern Victoria shows mixed Tasmanian and distal Gondwana detrital populations. The change in detrital zircon signature in western Tasmania suggests that VanDieland docked with the Australian continent during the Cambrian Tyennan Orogeny.